Environment and Natural resources conservation - Trivedi, P. R.; Sudarshan, K. N. (New Delhi : Commonwealth Publisher, 1994)
Environment and Natural Resources (ENR) works with all people and interested organizations to protect the environment by making sure resources are used wisely and that people understand their part in keeping the environment healthy. This business plan includes a departmental overview, information on responding to priorities, and a resource summary.--Includes text from document
Keywords: Conservation of natural resources -- India; Environmental protection -- India; Wildlife management -- India